The Effects Of Peer Group And Parents’ Parenting On Knowledge Of Free Sex At Smk N 1 Gedangsari Gunung Kidul - Nurhayani; Dinni Fitriani; Syarifah Sahirah (Jurnal Profesi Bidan Indonesia, 2023)
Background: Population Background: Adolescence is a period of sexual development. Ideally, at this period teenagers have acquired adequate knowledge about sex. Many teenagers do not know how to search for information about reproductive healthproperly. There is a tendency for teenagers to be more open to close friends than to their own parents. Reproductive health education for teenagers not only provides knowledge about reproductive organs, but the dangers of promiscuity, such as sexually transmitted diseases and so on. As a result, teenagers can avoid putting free sex to the test. Objective: This research is aimed at identifying the effects of peer group and parents’ parenting on knowledge of free sex at SMK N 1 Gedangsari Gunung Kidul. Methods: This is a descriptive analytical research with cross sectional approach. The sampling used simple random sampling with a sample size of 68 people. Data were collected using closed questionnaire. The research was conducted on May 18, 2015. The data were analyzed using chi-square and ordinal logistic regression.Results: The research results indicated significant effect between peer group and parents’ parenting on knowledge about free sex with p value of 0.000 (p <0.05) with a correlation coefficient of 0.517 and 0.568 ρ with medium cohesion. R Square value was 0.503. This means that 50.3% of knowledge about sex could be explained by the variable of peer group and parents’ parenting. Conclusion: There is a significant the effects of peer group and parents’ parenting on knowledge of free sex